2008
DOI: 10.1186/1748-5908-3-26
|View full text |Cite
|
Sign up to set email alerts
|

Toward a policy ecology of implementation of evidence-based practices in public mental health settings

Abstract: Background: Mental health policymaking to support the implementation of evidence-based practices (EBPs) largely has been directed toward clinicians. However, implementation is known to be dependent upon a broader ecology of service delivery. Hence, focusing exclusively on individual clinicians as targets of implementation is unlikely to result in sustainable and widespread implementation of EBPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
174
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 46 publications
0
174
0
Order By: Relevance
“…One area of intervention research where gaps exist is in understanding the processes of uptake of evidence-based practices. Recent research has suggested that clinicians may be constrained in adopting best practices by the ecology of their organizations, and that our field has relied too heavily on assigning responsibilities to clinicians alone (Raghavan et al 2008). Researchers conducting empirical studies of organizational-level interventions to increase the uptake of EBP approaches and improve client outcomes may help provide clinicians with needed agency support (Glisson et al 2016;Proctor et al 2011).…”
Section: Iqr Interquartile Rangementioning
confidence: 99%
See 1 more Smart Citation
“…One area of intervention research where gaps exist is in understanding the processes of uptake of evidence-based practices. Recent research has suggested that clinicians may be constrained in adopting best practices by the ecology of their organizations, and that our field has relied too heavily on assigning responsibilities to clinicians alone (Raghavan et al 2008). Researchers conducting empirical studies of organizational-level interventions to increase the uptake of EBP approaches and improve client outcomes may help provide clinicians with needed agency support (Glisson et al 2016;Proctor et al 2011).…”
Section: Iqr Interquartile Rangementioning
confidence: 99%
“…But the evidence base for treatment guidelines mainly is generated from specific diagnostic and symptom profiles, not the context in which individuals live. There is widespread acceptance of the importance of knowing about, and adopting, evidence-based practices, yet in day-today practice, under pressure from insurance companies and mental health organizations, clinicians must make rapid decisions about what treatment is likely to be most effective for a given client (Jensen-Doss et al 2009;Raghavan et al 2008); limited treatment research has been conducted in everyday practice settings to provide needed guidance for practitioners in the field (Weisz et al 2013). To date, there is little understanding of how clinicians make judgments about treatment effectiveness, and whether they use information beyond diagnostic symptoms to decide on the best treatment strategies.…”
mentioning
confidence: 99%
“…In contrast, practitioners who worked in settings without staff to manage housing applications (i.e., the CTI practitioner was responsible for managing the client's housing application) also sought to meet clients' needs and develop capacity for stable, independent living, but those efforts seemed to be easily compromised by the added responsibility related to housing applications. Although the way in which a setting with or without staff to manage housing applications affects clients' housing outcomes merits further research, this finding points to the importance of considering service structure as an essential element in the organizational ecology for CTI delivery (Raghavan, Bright, & Shadoin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for the implementation of the MHCC strategy on providing appropriate, accessible, coordinated and effective community mental health services will be the extent of comprehensive policy and funding to support these changes. As Raghavan, Bright, and Shadoin (2008) have noted, bridging the research-practice gap in public mental health settings involves policy changes with an ecological approach, i.e., efforts at multiple levels by multiple actors. Government policy makers, professional associations, cross-sectoral collaborations, client and family engagement, are some of the other critical elements.…”
Section: Discussionmentioning
confidence: 99%
“…First, core teams across all agencies participated in sessions on leading change and teamwork spanning two days based on organizational learning and change management approaches (Austin & Claassen, 2008 For personal use only. Botcheva et al, 2002;Brown et al, 2010;Edmondson, 2004;Hodson & Cooke, 2007;Raghavan, Bright, & Shadoin, 2008). Core teams were composed of individuals from all levels of the organization, including leadership, administrative, and front-line staff to ensure a high level of commitment throughout the agency.…”
mentioning
confidence: 99%